“N/A: NOT APPLICABLE”: Penal Policies and Female Psychiatric Custody in Bahia - Costa, Jessica Hind Ribeiro; Martins, Helena Loureiro (Argumentum, 2023)
This study aimed to understand what definition of health applies to treatments at Custody and Psychiatric Treatment Hospitals(HCTP), according to data from the State Plan for the Care of Women Deprived of Liberty and Released from the Prison System of Bahia (2018). For that, qualitative research, case study with literature review procedure and normative review were used. As a result, there is a definition of health attached to coping with illnesses, as biologists in the late 19th and early 20th centuries. From this understanding, the disregard of dimensions of the woman's state of biopsychosocial integrity stems from. Considering the HCTP and women's prisons as equivalent as total institutions, it is concluded that psychiatric patients have fewer social rights provided for in the Federal Constitution than those who are imprisoned.